Pengaruh Pemberian Ekstrak Bawang Dayak (Eleutherine palmifolia Merr.) dalam Air Minum terhadap Performa Ayam Broiler - Lisnawaty Silitonga; Satrio Wibowo; Metami Yulina Sirait (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
The aim of this study was to know the effect of giving dayak union (Eleutherine palmifolia Merr.) extract in drinking water on performance of broilers production. This research used Completely Randomized Design (CRD). The treatment was level of giving dayak union extract in drinking water (P0 = Drinking water without dayak union extract; P1 = Drinking water with 5% dayak union extract; P2 = Drinking water with 10% dayak union extract; P3 = Drinking water with 15% dayak union extract). The result showed that dayak union extract was significant (P0.05) to the proventriculus, long large intestine, liver, and heart. Giving 10% dayak union extract also decreased fat compound on broilers meat. Keywords: Performance of broiler chicken, dayak union extract, drinking water